Millennial identities as emerging ecumenical missional paradigm : a critical study of culture as a crisis and opportunity for mission - Counted, Agina Victor (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.